2004
DOI: 10.1073/pnas.0403824101
|View full text |Cite
|
Sign up to set email alerts
|

Emx2 homeodomain transcription factor interacts with eukaryotic translation initiation factor 4E (eIF4E) in the axons of olfactory sensory neurons

Abstract: We report that Emx2 homeogene is expressed at the mRNA and protein levels in the adult mouse olfactory neuroepithelium. As expected for a transcription factor, Emx2 is present in the nucleus of immature and mature olfactory sensory neurons. However, the protein is also detected in the axonal compartment of these neurons, both in the olfactory mucosa axon bundles and in axon terminals within the olfactory bulb. Emx2 axonal staining is heterogeneous, suggesting an association with particles. Subcellular fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 64 publications
3
58
0
4
Order By: Relevance
“…If one accepts the analogy between neurons and MDCK cells proposed by Dotti and Simons (25), this suggests that homeoproteins can be transported in the axons, released in the synaptic cleft, and recaptured at the post-synaptic level. In fact, Emx2 homeoprotein is transported into the axons of the olfactory receptor and accumulates in their terminals (26). Also in support of this idea is the recent demonstration that Otx2 homeoprotein can be transported from the retinal ganglion cells to interneurons of the visual cortex, with a relay in the dorsal thalamus (27).…”
Section: Discussionsupporting
confidence: 56%
“…If one accepts the analogy between neurons and MDCK cells proposed by Dotti and Simons (25), this suggests that homeoproteins can be transported in the axons, released in the synaptic cleft, and recaptured at the post-synaptic level. In fact, Emx2 homeoprotein is transported into the axons of the olfactory receptor and accumulates in their terminals (26). Also in support of this idea is the recent demonstration that Otx2 homeoprotein can be transported from the retinal ganglion cells to interneurons of the visual cortex, with a relay in the dorsal thalamus (27).…”
Section: Discussionsupporting
confidence: 56%
“…No evidence for the translation of odorant receptor or OMP mRNAs in sensory neuron axons has been reported thus far. Of particular interest, however, we have shown that the Emx2 homeodomain transcription factor is also transported into olfactory axons, where it interacts with the eIF4E translation initiation factor, a feature that suggests a regulated translation of mRNAs in these axons (Nédélec et al, 2004(Nédélec et al, , 2005. Furthermore, the observation of endogenous odorant receptors in the most distal segments of sensory axons within the olfactory bulb, but not in intermediate axon bundles connecting the epithelium to the bulb (Barnea et al, 2004;Strotmann et al, 2004), raises the question as to what molecular mechanisms control this intriguing axonal compartmentalization.…”
Section: Introductionmentioning
confidence: 99%
“…This regulation, first observed in growth cones, probably engages the mTOR pathway as it is accompanied by the phosphorylation of eIF4E and 4E-BP1, two key regulators of protein translation 11 . Regulating translation may be a property of several homeoproteins since many of them, including Engrailed, bind eIF4E 12,13 .…”
Section: Introductionmentioning
confidence: 99%